Instruments and schemes of in-service mathematics teachers during the design of teaching based on questioning - Otero, Maria Rita (2022)
This work analyzes the instruments and schemes of 55 in service teachers of mathematics, generated during an online university course where they were proposed to study the generating question of a study and research path (SRP) and design teaching from it. The theoretical framework of the research is the theory of conceptual fields (TCF) and the instrumental approach. The situation in which teachers should make a teaching proposal with this resource and what knowledge they would teach is analysed. The objective is to describe the schemes of use and the instruments generated by them, focusing on the components of the schemes and the operational invariants generating the teaching activity when teachers conceive the teaching proposal. The results allow us to understand the difficulties of teaching in the questioning paradigm.